Importance of diet in children and adolescents with obesity and asthma - Monika Soczewka; Andrzej Kędzia; Bogda Skowrońska; Elżbieta Niechciał (Pediatric Endocrinology, Diabetes and Metabolism)
Both obesity and asthma are increasingly being diagnosed in the childhood population. Obesity is linked to a greater asthma morbidity, and it increases the risk of severity of the disease course. The association between these 2 disorders has not yet been fully elucidated; however, several putative factors have been proposed related to mechanical and inflammatory aspects of obesity. Diet is an important adjustable element in obesity and asthma management. An unhealthy diet based on processed food is likely to promote chronic inflammation in both conditions; hence, appropriate nutrition should be an integral part of the children's therapy. This review discusses dietary models that have a positive impact on patient health.